COMBINED CONVECTION HEAT TRANSFER TO THERMALLY DEVELOPING FLOW IN HORIZONTAL CIRCULAR CYLINDER (مجلة الهندسة, 2006)
Experiments were conducted to study the local and average heat transfer by mixed convection for hydrodynamically fully developed but thermally developing laminar air flow in horizontal circular cylinder. The experimental setup using an aluminum cylinder as test section with 30 mm inside diameter and 900 mm heated length (L/D=30), is subjected to a constant wall heat flux boundary condition. The investigation covers Reynolds number range from (400 to 1600), heat flux varied from (60W/m² to 400W/m²)and by using an aluminum entrance section pipes (calming sections) having the same inside diameter as test section pipe but with variable lengths as entrance sections. The entrance sections included a long calming section of length 240 cm (L/D=80) and two short calming sections with lengths 60 cm (L/D=20), 120 cm (L/D=40). The results present the temperature variation along the cylinder surface and the local and average Nusselt number variation with the dimensionless axial distance (Z). For all entrance sections, the results show an increase in the Nusselt number values as the heat flux increases. Also, the mixed convection regime can be bounded by a suitable selection of (Re) number ranges and the heat flux ranges. The obtained Richardson numbers (Ri) range varied approximately from (0.1171 to 12.54).